2016
DOI: 10.1007/s11356-016-6318-9
|View full text |Cite
|
Sign up to set email alerts
|

Repellent and mosquitocidal effects of leaf extracts of Clausena anisata against the Aedes aegypti mosquito (Diptera: Culicidae)

Abstract: Mosquitoes are rapidly developing resistance to insecticides that millions of people relied on to protect themselves from the diseases they carry, thereby creating a need to develop new insecticides. Clausena anisata is used traditionally as an insect repellent by various communities in Africa and Asia. For this study, the repellency and adulticidal activities of leaf extracts and compounds isolated from this plant species were evaluated against the yellow fever mosquito, Aedes aegypti. In the topical applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
9
0
2
Order By: Relevance
“…Adult mortality ranging from 4 to 10% after 24 hours of exposure was reported. A report from India further affirms this adulticidal activity (Ramkumar et al, 2015) In the study by Mukandiwa et al (2016b) the acetone and hexane leaf extracts of C.…”
Section: Adulticidal Activitymentioning
confidence: 85%
See 3 more Smart Citations
“…Adult mortality ranging from 4 to 10% after 24 hours of exposure was reported. A report from India further affirms this adulticidal activity (Ramkumar et al, 2015) In the study by Mukandiwa et al (2016b) the acetone and hexane leaf extracts of C.…”
Section: Adulticidal Activitymentioning
confidence: 85%
“…The adulticidal activity of C. anisata against mosquitoes has been reported by Mavundza et al (2014) and Mukandiwa et al (2016b). Of note again, is the fact that the different researchers used different methods to demonstrate the cidal effect of C.…”
Section: Adulticidal Activitymentioning
confidence: 91%
See 2 more Smart Citations
“…Hook. f. ex Benth., are widely used by local people for ethnomedicinal and other purposes (Albaayit et al 2016;Mukandiwa et al 2016aMukandiwa et al , 2016b. Phytochemical studies on Clausena species revealed the preponderance of prenylated/geranylated coumarins and carbazole alkaloids with interesting bioactivities (Ito et al 2000;Sripisut et al 2012;Cao et al 2018;Yan et al 2019).…”
Section: Introductionmentioning
confidence: 99%